BAHASA TUBUH DALAM KARYA SENI PATUNG REALISME - BENO BANIANTO, Dra. Lisa Widiarti, M.Sn., Drs. Erfahmi, M.Sn. (Universitas Negeri Padang, 2018)
the purpose of creating works of art is to know the extent to which body language plays a role in human social life as the delivery of nonverbal messages, and to present works of sculptures that look at body pieces and visualize works by using a realist style. Method of cultivating results in the idea of art ideas in the creation process are among others: Preparation, elaboration, synthesis, concept realization, and completion. The results of the process through the idea into the form of sketches designed in such a way Based on the photographs made sketches which then consulted to the supervisor when it was getting the concept of work then visualize it in the form of a realist sculpture. the final stage of the process of making works where the author is ready to visualize into a final work as a condition for completing the degree program of art education.Keywords: Body Language, Statue, Realist.